Determinant of Family Takaful Adoption Among Puncak Alam Residents - Mohd Rasid, Mohd Faizol Rizal; Ruslan, Ainol Fizy (Information Management and Business Review, 2024)
This study investigates the key determinants influencing the adoption of family takaful among residents of Puncak Alam, Selangor. Despite the strategic design of family takaful to provide financial protection, particularly for low-income earners in the event of financial loss, its market penetration in Malaysia remains low. This raises important questions about the barriers to its widespread adoption, despite extensive promotional efforts by the takaful industry. The research aims to address these challenges by identifying and analyzing the factors that hinder the broader uptake of family takaful. A quantitative and descriptive research approach was adopted to gain a deeper understanding of the issue. Data collection was conducted using random sampling techniques, and the responses were analyzed using descriptive statistics with the help of the Statistical Package for Social Sciences (SPSS) software. The study involved a structured survey of 100 respondents from Puncak Alam, which examined the impact of three key variables - price, knowledge, and satisfaction - on the adoption of family takaful. The findings of this study underscore the significance of these three factors in shaping consumers’ decision-making processes regarding family takaful. Price, as an indicator of affordability, knowledge about family takaful products, and the level of satisfaction with existing services, were all found to significantly influence adoption rates. By highlighting these critical determinants, the research provides valuable insights for policymakers, takaful operators, and financial service providers to refine their strategies and promote wider adoption of family takaful, ultimately enhancing financial security for the Malaysian population.